Pengaruh Profitabilitas, Struktur Modal, Likuiditas Terhadap Nilai Perusahaan Sektor Perdagangan, Jasa, Dan Investasi - Janshen Patrick, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this study is to obtain empirical evidence about the influence of profitability, capital structure, likuidity and firm value in trade, service, and investment sector on the Indonesia Stock Exchange period 2015-2019. This research is done by using purposive sampling method and obtained 54 companies for the sample. For the data processing is using program name Eviews, version 10. The result showed that profitability variables have a positive and significant effect on firm value. Capital structure variables have a positive and significant effect on firm value. Likuidity variables have a positive and not significant effect on firm value. The implication of this study is to increase the profitability and capital structure to increase the firm value which will bring a good signal for investors.